Right Atrial Clot Formation Early after Percutaneous Mitral Balloon Valvuloplasty - Ateş, Ahmet Hakan (Case Rep Med, 2016)
Mitral balloon valvuloplasty which has been used for the treatment of rheumatic mitral stenosis (MS) for several decades can cause serious complications. Herein, we presented right atrial clot formation early after percutaneous mitral balloon valvuloplasty which was treated successfully with unfractioned heparin infusion.